Theorizing the dynamics of social processes - Dahms, Harry F.; Hazelrigg, Lawrence (Bingley, U.K. : Emerald, 2010)
The chapters in this volume represent steps in the direction of demonstrating the importance of efforts to theorize the dynamics of specific social, cultural, political, and/or economic processes to the social sciences in general. They aim to clarify how those efforts are central to the core mission of each of the social sciences, and how social theory is both especially well positioned to tackle this challenge and to accept responsibility for illuminating related possibilities. Papers address the nature and importance of "process" in studying modern (industrialized, post-industrial, capitalist, postmodern, globalizing, etc.) societies at macro, meso, or micro-scale. The volumes overall purpose is to assemble a set of essays that invent, develop, and/or demonstrate strategies for theorizing one or several dynamic processes, so as to identify, illustrate by example, and analyze specific problems as well as connect theorizations of process across different disciplines of inquiry.
Introduction / Harry F. Dahms and Lawrence Hazelrigg -- On theorizing the dynamics of process : a propaedeutic introduction / Lawrence Hazelrigg -- Affinities between the project of dynamic theory and the tradition of critical theory : a sketch / Harry F. Dahms -- History and the processing of class in social theory / Joseph Maslen -- Domination, contention, and the negotiation of inequality : a theoretical proposal / Viviane Brachet-Márquez -- The labor-value relation and its transformations : revisiting Marx's value theory / Paul Paolucci -- Globalization in and out, or, How can there be a constructivist theory of globalization? / Jean-Sébastien Guy -- Conceptualizing globalization in terms of flows / P.J. Rey and George Ritzer -- Why Nazified Germans killed Jewish people : insights from agent-based modeling of genocidal actions / Robert B. Smith -- Economy and field in the rise of postmodern architecture / David Gartman.
Print version record
Keywords: Social Science -- Sociology -- General; Social Science -- Research; Social Science -- General; Social theory; Sociology; Social sciences -- Research; Social sciences -- Philosophy